Identification of long non-coding RNAs involved in floral scent of Rosa hybrida - Shi, Shaochuan; Zhang, Shiya; Wu, Jie; Liu, Xintong; Zhang, Zhao (Frontiers in Plant Science, 2022)
Long non-coding RNAs (lncRNAs) were found to widely exist in eukaryotes and play important roles in various biological processes. Rose is economically important because of their wide use for garden and cut flowers as well as important sources of natural fragrance for perfume and cosmetics industry. However, the regulatory mechanism for floral scent production in rose was little known, hindering the breeding to improve their scent attribute. Therefore, the identification and characterization of lncRNAs involved in the floral scent synthesis would not only help us to understand floral scent production but also provide genetic elements for producing scented rose. In the present study, a RNA-Seq analysis was performed for rose flowers in different flowering stages, using strand-specific libraries. By using scented variety ‘Tianmidemeng’ was used as plant material, a total of 13,957 lncRNAs were identified by mining the RNA-Seq data, including 10,887 annotated lncRNAs and 3,070 novel lncRNAs. The identified lncRNAs had lower abundance, fewer exons, and shorter lengths when compared to protein-coding genes. A total of 29,622 genes were predicted to be targets of the 10,075 lncRNAs, including 54 synthase genes and 24 transcription factors related to floral scent synthesis. 425 lncRNAs were differentially expressed during the flowering process, among which 19 were differentially expressed among all the three flowering stages. We further quantified floral scent compounds by using GC-MS analysis. In addition, we used Weighted correlation network analysis (WGCNA) to correlate the differentially-expressed lncRNAs to individual floral scent compounds, this allowed us to identify lncRNAs directly related to the different floral scent metabolites. In this study, we were able to show that lncRNAs may play important roles in floral scent production in the rose. This study also improves our understanding of how plants regulate their secondary metabolism by using lncRNAs.